Trends in Neuroendocrinology - Hubert Vaudry (Frontiers Research Topics, 2016)
Neuroendocrinology is the discipline that investigates the interplay between the nervous and endocrine systems i.e. the control of endocrine glands by the central and peripheral nervous systems, the action of hormones on nerve cells and the production of hormones by the nervous system. The present Research Topic is a compilation of contributions stemming from the 8th International Congress of Neuroendocrinology (ICN2014) held in Sydney, Australia, that illustrates various facets of current neuroendocrine research.